LAND INHERITANCE AND ITS RELATION TO AGRICULTURAL DEVELOPMENT IN ONDO DIVISION, WESTERN STATE, NIGERIA (1972)
The study was aimed at finding the relationship between land inheritance and agricultural development in Ondo division of Western State of Nigeria. Chapter one was devoted to the review of the economy of Western State, the requisites for agricultural development and the relationship between land inheritance and the requisites for agricultural development. The nature of our problem was considered in relation to the present mode of production, the rising population and the probable land shortage. Chapter two was devoted to the methodology and the setting of the thesis. Among others, it considered reasons for choosing Ondo division for a case study, the sources of data and their limitations. Chapter three considered land inheritance in theory and in practice. It reviewed the various meanings and interpretations of inheritance. Finally, we considered case studies of some selected countries. Chapter four was devoted to the analysis of the situation in Ondo division. It was divided into three sections. The first part discussed the inheritance pattern in Ondo division, the second part discussed agriculture and the third part related inheritance to agricultural development. Chapter five was devoted to the policy implication of the study. Our recommendations in this chapter include: (l) The imposition of death duties proportional to number of plots (2) Empowering local authorities to control the farms of those who die without wills. (3) That state farms organised as joint-stock companies should he introduced, where the government and farmers would he shareholder (4) That multi-cooperatives should he encouraged. (5) That individual ownership should he encouraged. Chapter six was devoted to the summary of the thesis. Major findings summarised in the chapter include (1) That land inheritance merely accentuates the process of fragmentation of holdings. Main causes were found to be the techniques of cultivation and safety in face of dangerous animals. (2) That the presence of the part-time farmers in farming, instead of being to the detriment of agriculture, is a blessing, since they bring innovation and capital to agriculture. However, in some cases, it leads to the growth of absentee landlordism. (3) That injection of capital and its efficient use in agriculture is impeded by aversion to borrowing, unwillingness to use inherited lands as collateral and the small sizes of farms. (4) That strangers though permitted in some cases to own farms, cannot decide to transfer their lands as they wish, (5) That consolidation of holdings may not be the answer to the fragmentation of holdings in this area, since in our situation, the farms to be consolidated involve cash-crops of varying ages.